Prevalencia de hematuria enzoótica en bovinos sacrificados en el camal municipal de Balsas - Ramírez Asanza, Carlos Julio (2006)
For this investigation one carries out a study on 500 animal slaughterer in the municipal slaughterhouse of Rafts. The percentage of opposing positive was of 23.8%. The diagnosis made it to him microscopically, impacting the bladders and observing if they were or not positive. The females reached a high percentage of positive animals with 40.23%, in front of 5.85% of the males. as for the age, the females bigger than 5 years were those but affected with a 47. 69%. There were not significant differences as for the positive percentages among races. The place with the percentage but high of prevalence you was San José with 45.45%